NEGOTIATING HYBRID IDENTITY: THE MUHAMMAD CHENG HOO MOSQUE AND CHINESE MUSLIM COMMUNITY INTEGRATION IN BERASTAGI - Artanti, Nabilah Aprilia; Ismail, Ismail; Muary, Rholand (Jurnal Al-Ijtimaiyyah, 2026)
This study examines how the Muhammad Cheng Hoo Mosque in Berastagi symbolizes Chinese Muslim identity within a predominantly non-Muslim Karo society, addressing a gap in understanding hybrid identity formation among "double minority" groups in non-Muslim majority contexts. Employing a qualitative ethnographic approach grounded in Peter L. Berger's sociology of religion — specifically his social construction of reality framework — and interpretive symbolic anthropology, data were collected through participant observation, in-depth interviews with ten key informants comprising a mosque founder and nine Chinese Muslim converts, and historical document analysis. Data were analyzed using Peirce's semiotic framework, operationalizing architectural elements as icons, indices, and symbols of hybrid cultural meaning. The findings reveal that the mosque's distinctive architecture — featuring red-gold color palettes and pagoda-style roofs integrated with Islamic spatial principles — functions as a visual manifestation of hybrid identity through the processes of externalization, objectivation, and internalization. Beyond its ritual function, the mosque operates as a strategic public space enabling the Chinese Muslim minority to express dual identity, strengthen internal cohesion, and navigate their "double minority" status in a Karo-majority environment. The inclusive spatial design fosters inter-ethnic tolerance and religious harmony, receiving support from local authorities and cross-religious figures despite demographic asymmetry. This study contributes to Islamic Community Development scholarship in multicultural settings by demonstrating that culturally-adapted religious architecture can serve as a non-confrontational mechanism for minority resilience, social integration, and intergenerational transmission of hybrid identity, while maintaining full Islamic theological integrity.